Child Soldiers and United Nations Sustainable Development Goals - Donmez, Suat (Border Crossing, 2023)
The United Nations' eighth Sustainable Development Goal (SDG) focuses on “decent work and economic growth.” A primary objective of this goal is to urgently and effectively eradicate severe forms of child labour. This initiative includes abolishing forced labour, ending modern slavery and human trafficking, and preventing children's use as soldiers. Historically, children have been significantly impacted by the devastating effects of wars, being exploited for various military activities globally. Currently, child soldiers, irrespective of gender, participate in civil wars and conflicts in numerous countries worldwide. Despite the United Nations classifying the military recruitment of child soldiers as a war crime, thousands of children actively participate in conflicts. A significant portion of child soldiers are girls, often subjected to sexual slavery and forced into “marriages” with male combatants. A crucial concern regarding child soldiers is their retraining and reintegration into society. Another significant consideration is the classification of these children — whether they should be viewed as criminals or victims. This study explores the global use of child soldiers, specifically in some instances. A pivotal aspect of this examination is understanding the international legal framework, UN SDGs and the Disarmament, Demobilization and Reintegration process. These models, implemented by the United Nations in partnership with local governments, aim to reintegrate post-conflict children, both boy and girl child soldiers.